The major cell surface glycoprotein procycline is a receptor for induction of a novel form of cell death in African trypanosomes in vitro - Pearson, T.W.; Beecroft, R.P.; Welburn, S.C.; Ruepp, S.; Roditi, I.; Kuo-Yuan, H.; Englund, P.T.; Wells, C.W.; Murphy, N.B. (Elsevier, 2000)
Bloodstream forms (BSF) and procyclic culture forms (PCF) of African trypanosomes were incubated with a variety of lectins in vitro. Cessation of cell division and profound morphological changes were seen in procyclic forms but not in BSF after incubation with concanvavalin A (Con A). Wheat germ agglutinin and Ricinus communis agglutinin. These lectins caused the trypanosomes to cease division, become round and increase dramatically in size, the latter being partially attributable to the formation of what appeared to be a large 'vacuole-like structure' or an expanded flagellar pocket. Con A was used in all further experiments. Spectrophotometric quantitation of extracted DNA and flow cytometry using the DNA intercalating dye propidium iodide showed that the DNA content of Con A-treated trypanosomes increased dramatically when compared to untreated parasites. Examination of these cells by fluorescence microscopy showed that many of the Con A-treated cells were multinucleate whereas the kinetoplasts were mostly present as single copies, indicating a disequilibrium between nuclear and kinetoplast replication. Immunofluorescence experiments using monoclonal antibodies (mAb) specific for paraflagellar rod proteins and for kinetoplastid membrane protein-11 (KMP-11), showed that the Con A-treated parasites had begun to duplicate the flagellum but that this had only proceeded along part of the length of the cells, suggesting that the cell division process was initiated but that cytokinesis was subsequently inhibited. Tunicamycin-treated wild-type trypanosomes and mutant trypanosomes expressing both high levels of non-glycosylated procyclins and procyclin isoforms with truncated N-linked sugars were resistant to the effects of Con A. suggesting that N-linked carbohydrates on the prarasites created by deletion of all three EP procyclin isoforms, two of which contain N-glycosylatin sites, by homologous recombination. The knockout mutants showed reduced binding of fluorescein-labelled con A as determined by flow cytometry and were resistant to the effects of Con A. Taken together the results show that Con A induces multinucleation, disequilibrium between nuclear and kinetoplast replication and a unique form of cell death in procyclic African trypanosomes and that the ligands for Con A binding are carbohydrates on the EP forms of procyclin. The possible significance of these findings for the life cycle of the trypanosomes in the tsetse fly vector is discussed.